2010
DOI: 10.3174/ajnr.a1851
|View full text |Cite
|
Sign up to set email alerts
|

C-Arm CT Measurement of Cerebral Blood Volume in Ischemic Stroke: An Experimental Study in Canines

Abstract: BACKGROUND AND PURPOSE:CBV is a key parameter in distinguishing penumbra from ischemic core. The purpose of this study was to compare CBV measurements acquired with standard PCT with ones obtained with C-arm CT in a canine stroke model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 15 publications
(15 reference statements)
0
45
0
1
Order By: Relevance
“…This would facilitate the assessment of hemodynamic relevance of the stenotic lesion in addition to quantification of restenosis. 28 In our study, ivACT showed a high sensitivity and specificity for the detection of ISR compared with iaDSA. We could successfully detect and quantify ISR on ACT images in all 5 patients presenting an ISR at follow-up iaDSA.…”
Section: Resultsmentioning
confidence: 88%
“…This would facilitate the assessment of hemodynamic relevance of the stenotic lesion in addition to quantification of restenosis. 28 In our study, ivACT showed a high sensitivity and specificity for the detection of ISR compared with iaDSA. We could successfully detect and quantify ISR on ACT images in all 5 patients presenting an ISR at follow-up iaDSA.…”
Section: Resultsmentioning
confidence: 88%
“…This then offers a potential alternative to the use of an IV injection of contrast when CBV measurements are made using C-arm CT. 6,7 We have also shown that, in the canines with acute ischemia, regional measurement of CBV in conjunction with either a CCA or a VA injection of contrast was not a reliable method for providing CBV maps. In normal canines, however, the CCA and VA injection routes did provide regional CBV maps that were comparable with ones obtained with standard PCT.…”
Section: Discussionmentioning
confidence: 99%
“…24 Third, it has been demonstrated, in animals and in humans, that by using C-arm CT, measurements of CBV can be obtained that compare well with those made by using standard PCT. [6][7][8][9] Finally, as we, and others, have previously noted, the potential to perform repeated assessments of perfusion parameters during an intervention seemingly would improve the ability of an operator to not only assess the effectiveness of treatment in an ongoing fashion-that is, whether a CBV abnormality is stable or whether it is becoming smaller-but also provide some insight into the benefit and risk of continuing an intervention, that is, whether the CBV abnormality is larger despite the intervention. The ability to perform these measurements on a regional basis, using injections of contrast through an existing catheter upstream from ischemic tissue, would seemingly further enhance the value of this capability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations